RESEARCH OF METHODICAL BASE OF COST MANAGEMENT FOR EFFECTIVE USE AT PROJECT COST MANAGEMENT - Y. Vorontsova; A. Geokchakyan; N. Mahova (Вестник университета)
In the article the methodical base of cost management is investigated, the techniques suitable for effective project cost management are chosen areas of their expedient use and tasks solved with their help are defined. The conceptual plan of project cost management developed by authors including development stages and realization of formation of costs of the project depending on his look (small, average or the megaproject) and financing sources is presented in article (state or commercial). The "economic justification of the created project cost" block including the analysis of the end results and possible adjustments is allocated. Scientific novelty is represented by the tools offered in article for effective monitoring of process of project cost formation on the basis of the created limits of minimum possible and most admissible expenses.